Change in practice after the Surfactant, Positive Pressure and Oxygenation Randomised Trial. Issue 5 (29th May 2014) - LeVan, Jaclyn M; Brion, Luc P; Wrage, Lisa A; Gantz, Marie G; Wyckoff, Myra H; Sánchez, Pablo J; Heyne, Roy; Jaleel, Mambarambath; Finer, Neil N; Carlo, Waldemar A; Das, Abhik; Stoll, Barbara J; et al.
Abstract : Objective: To test the hypothesis that the proportion of endotracheal intubation (ETI) in the delivery room (DR) decreased in Neonatal Research Network (NRN) centres after the National Institute of Child Health and Human Development NRN Surfactant, Positive Pressure, and Oxygenation Randomised Trial (SUPPORT). Design: Retrospective cohort study using the prospective NRN generic database. Setting: Eleven centres that participated in the SUPPORT trial and remained part of the NRN. Preterm neonates 24 0/7 –27 6/7 weeks' gestational age enrolled in the SUPPORT trial were randomised to: (1) DR continuous positive airway pressure or DR ETI with early surfactant administration; and (2) oxygen saturation targets of 85–89% or 91–95%. The prior NRN feasibility trial had assessed the feasibility of randomisation to continuous positive airway pressure versus ETI. Patients: Infants 24 0/7 –27 6/7 weeks' gestational age, excluding infants with syndromes or major malformations and those on comfort care only. Main outcome measure: Proportion of DR ETI. Results: The proportion of DR ETI decreased significantly in the group of infants from centres that had not participated in the feasibility trial (91% before vs 75% after SUPPORT, adjusted relative risk 0.86, 95% CI 0.83–0.89, p<0.0001) but not in the group of infants from the other centres, where the proportion of ETI was already lower prior to initiation of the SUPPORT trial (61% before vs 58% after SUPPORT, adjusted relative risk 0.96, 95% CI 0.89 to 1.05, p=0.40). Conclusion: This study shows that DR ETI changed after SUPPORT only in NRN centres that had not participated in a similar trial. Trial registration number: NCT00063063 (GDB) and NCT00233324 (SUPPORT).